Conversion index for running on different indoor track and field facility types - Barnes, K. R.; Malcata, R. (International Journal of Performance Analysis in Sport, 2017)
There are many variations of sizes for indoor running tracks, which have caused difficulty in setting fair and equitable qualifying standards for championship competitions. The aim of this study was to determine event- and gender-specific conversions by indoor track facility type for standard running events ranging from 200 to 5000 m. All performances for running events were obtained from 2010 to 2015 using the Track and Field Results Reporting System. Conversions between track types were determined as factor differences using a mixed modelling approach in SAS for gender and event separately. A total of 325,074 performances (162,176 male, 162,898 female) on 184 flat, 19 banked, 36 oversized and 21 undersized tracks were included in the analysis. All conversion standards with 90% confidence intervals for men and women presented were clear. For all events and both genders, converting from an undersized track to all other track types resulted in faster race times (conversion < 1.0), flat to banked and flat to oversized tracks also resulted in faster race times (conversion < 1.0) and banked and oversized to flat tracks resulted in slower race times (conversion > 1.0). Overall, there is a significant track effect between facility types for both genders and most facility types.